Convergences and divergences among student expectations and training in accordance with the National Curriculum Guidelines for Medicine (Research, Society and Development, 2022)
The objective of study was to analyze formative expectations of medical incoming students in a public university, under the perspective of National Curriculum Guidelines (NCG) in Medicine. This is a qualitative study using a guide-script and a recorded interview with new medicine students at the State University of Ponta Grossa, in 2019. The sample was defined by the saturation method. After transcription, the data were analyzed by thematic content analysis by three independent researchers, and then there was the grouping between the categories and subcategories identified in accordance with the NCG for Medicine. Among the interviewees, three were women and ten men, aged between 17 and 26 years, of which 30% entered the course through affirmative action policy. The analysis showed three categories and five subcategories: Health Care (humanist training and social responsibility), Health Management (general training and decision-making) and Health Education (continuing education). Despite a thought for a more humanistic and socially responsible training, important resources are still lacking in the thought of attention to the other minimum requirements for training according to the NCG of future doctors, since items necessary for an integral training were not discussed, and a clear concern centered on the capacity for technical knowledge and mainly on logical reasoning for the diagnosis, that is, little grounded in knowledge about prevention and promotion actions, and more focused on recovery and rehabilitation.